Manufacturing and High Heat Flux Testing of Brazed Flat-Type W/CuCrZr Plasma Facing Components - 练友运 刘翔 封范 陈蕾 程正奎 王金 谌继明 (Plasma science & technology, 2016)
Water-cooled flat-type W/Cu Cr Zr plasma facing components with an interlayer of oxygen-free copper（OFC） have been developed by using vacuum brazing route.The OFC layer for the accommodation of thermal stresses was cast onto the surface of W at a temperature range of 1150oC-1200 oC in a vacuum furnace.The W/OFC cast tiles were vacuum brazed to a Cu Cr Zr heat sink at 940 oC using the silver-free filler material Cu Mn Si Cr.The microstructure,bonding strength,and high heat flux properties of the brazed W/Cu Cr Zr joint samples were investigated.The W/Cu joint exhibits an average tensile strength of 134 MPa,which is about the same strength as pure annealed copper.High heat flux tests were performed in the electron beam facility EMS-60.Experimental results indicated that the brazed W/Cu Cr Zr mock-up experienced screening tests of up to 15 MW/m~2 and cyclic tests of 9 MW/m~2 for 1000 cycles without visible damage.